Evaluation of Physicochemical Properties and Mineral Content of some Indigenous Spices Retailed in Ibadan, Nigeria - Yewande BAMIGBOYE, Adeola; Thomas ADEPOJU, Oladejo; Oluwaseun OLADIPO, Peter (International Journal of Nutrition, 2020)
Spices have been frequently added to foods since ancient times, not only to enhance the taste but also as preservatives and medicinal agents. Their usage may be of concern due to possible contamination during processing and handling. The aim of this study was to investigate the physicochemical properties and heavy metals concentrations in some indigenous spices sold at two main markets namely Bodija and Apata markets in Ibadan, Oyo State, Nigeria. A total of eight commonly consumed spices were purposely analyzed for their proximate and mineral composition, physicochemical properties and anti-nutrients contents. Proximate analyses showed that the spices to contained (fresh matter ‘As consumed’) moisture content ranging from 11.74g in thyme to 59.36g/100g in scent leaves. Crude protein, fat, fibre, ash and carbohydrate contents ranged between 3.72 – 15.07g, 1.31 – 8.28g, 1.96 – 11.38g, 1.11 – 7.81g, and 17.80 – 50.77g/100g sample, respectively. All the spices contained high levels of potassium (176.3 – 739.6 mg), sodium (60.6 – 317 mg), calcium (78.5 – 423.9 mg), magnesium (82 – 322.1 mg) and iron (5.78 – 20.10 mg), but low levels of heavy metals – copper (0.17 – 0.68 mg), and manganese (0.32 – 1.05 mg)/100g respectively. Flavonoid was the most abundant phytochemical, while terpene was the least phytochemical in all the samples. The samples had very low concentrations of anti-nutrients, and could pose no threat to human health, as their values were within the regulatory standard. The antioxidants and phytochemicals in the spices can help in building up immunity and prevention of non-communicable diseases, hence, their consumption should be encouraged.
Keywords: Spices; Physico-chemical properties; Phytochemicals; Anti-nutrients.